2019
DOI: 10.1111/1745-5871.12361
|View full text |Cite
|
Sign up to set email alerts
|

An integrated assessment of China's South—North Water Transfer Project

Abstract: Key insightsThe SNWTP is producing highly uneven regional effects. Its environmental performance is also mixed. An integrated assessment of the SNWTP problematises the role of interbasin transfers in sustainable water supply.[Correction added on 5 th February 2020, after first online publication: The key insight section was included] AbstractChina's South-North Water Transfer Project (SNWTP) is a vast and still expanding network of infrastructure and institutions that moves water from the Yangtze River and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Some wells observed the GWS recovery during 2005–2014 (e.g., in Cangzhou City; Figure 6a), which was related to the success of localized groundwater management (Shang et al, 2016). A majority of wells in Beijing City observed the GWS recovery during 2015–2018 (Figure 6b), which was attributed to the reduction of Q p jointly caused by the replacement of Q d and the steady increase of recycled water use (He et al, 2019; Long et al, 2020; Rogers et al, 2019; S. Wang et al, 2019). Figure 6c shows the 2005–2018 monthly time series of GWS variations in NCP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some wells observed the GWS recovery during 2005–2014 (e.g., in Cangzhou City; Figure 6a), which was related to the success of localized groundwater management (Shang et al, 2016). A majority of wells in Beijing City observed the GWS recovery during 2015–2018 (Figure 6b), which was attributed to the reduction of Q p jointly caused by the replacement of Q d and the steady increase of recycled water use (He et al, 2019; Long et al, 2020; Rogers et al, 2019; S. Wang et al, 2019). Figure 6c shows the 2005–2018 monthly time series of GWS variations in NCP.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the recovery of groundwater level has been reported in some locations. For example, a recovery of 9 m from 2014 to 2017 was observed in the Huairou Waterworks in Beijing (He et al, 2019; Long et al, 2020; Rogers et al, 2019; S. Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Indian ILR project will directly transfer water between India and Nepal, and will indirectly impact Bangladesh rivers, even though no direct IBWT infrastructure crosses into Bangladesh itself (Amarasinghe and Sharma, 2008;Misra et al, 2007). Rogers et al (2019) evaluated the potential impacts of China's ongoing South-North Water Transfer Project (SNWTP) and concluded that continuous, long-term evaluation of socio-economic, environmental, and political impacts are necessary to truly understand the project's implications.…”
Section: Critiques Of Ibwtmentioning
confidence: 99%
“…The east route of the SNWD project passes through three provinces and one municipality (Jiangsu, Shandong, Hebei Provinces, and Tianjin Municipality) and Xuzhou city in Jiangsu Province is a hub city of the east route [ 6 ]. Xuzhou is located at the border of Jiangsu Province, which is mainly water supply area, and Shandong province, which is mainly a water use area.…”
Section: Introductionmentioning
confidence: 99%